Human Resource Competence with Capacity Development: The Perspective of E-Assessment and E-Learning - Cut Aviyanti; Zahara Tussoleha Rony; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2024)
This research aims to provide an overview of the systematic findings of dozens of pieces of literature compiled to strengthen the variables in this research. The research method applied in this scientific article is a structured literature review. Relevant scientific articles were selected, identified, and evaluated during the literature review process. Determination of study scope was carried out using the PICO (population/problem, intervention, comparison) framework, which provides a score to determine study boundaries. Providing research results that are far from perfect as an illustration of the research results and also a reference for continuing this research with various types of the same variables with different objects. Keywords: Information Technology, HR Competence, Institutional, Capacity Development, E-Learning, E-Assessment